Improving Adolescent Health Through Digital Youth Capacity Building - Hani Handayani; Neni Sholihat; Sri Mulyanti; Asep Setiawan; Heri Budiawan (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The complexity of adolescent health problems, of course, requires a comprehensive and integrated handling that involves all elements from across related programs and sectors. The Ministry of Health has developed Adolescent Care Health Services (PKPR) at Puskesmas, with a comprehensive package of services for adolescent health including IEC, counseling, coaching peer counselors, clinical/medical services and referrals including community empowerment. The purpose of this community service activity is to increase the capacity of cadres in managing adolescent posyandu. It is hoped that with community service activities, in the form of assistance and capacity building for adolescent posyandu cadres, it will spur community development, especially adolescents there by fostering their own motivational power, as well as being agents of change and preparing development cadres, after the formation of adolescent posyandu in the area. This Community Service activity, not only in the form of workshops to cadres that have been carried out, but will be followed by the provision of on the spot services in RW Palahan Setiamulya Village Tamansari District Tasikmalaya City. The activity of providing health test services for adolescents, will be carried out by students, cadres of Hizbul Wathon and lecturers of the Faculty of Health Sciences, University of Muhammadiyah Tasikmalaya.